Dementia and Diabetes Mellitus in Porto-Novo: Frequency and Determining Factors. - WANVOEGBE, FINANGNON ARMAND; GNONLONFOUN, DIEU-DONNÉ; AGBODANDE, KOUESSI ANTHELME; AZON ÉPSE KOUANOU, ANGÈLE (My University, 2021)
Background: Chronic hyperglycemia promotes the development of degenerative diseases such as dementia. Our objective is to study dementia in diabetic patients in a hospital environment in Porto-Novo. Methods: This is a cross-sectional, prospective study with a descriptive and analytical aim that took place from May 18 to September 18, 2017, i.e . 4 months. The study population consists of all diabetic patients who consulted in the internal medicine departments of the Oueme-Plateau Teaching Hospital and at Saint Gérard clinic in Porto-Novo during the study period and who gave their enlightened consent. Results: The study included 246 patients with a mean age of 56.47 ± 11.97 years. There were 172 (69.9%) women, i.e. a sex ratio of 0.43. Diabetes had been known for less than 10 years in the majority (67.9%). Type 2 diabetics were in the majority (95.5%). Of the 246 patients, 42 (17.1%) had a Mini Mental State Examination (MMSE) less than or equal to 24. Of these 42 patients, 32 met the DSM V (Diagnostic and Statistical Manual disorders, 5th edition) criteria for dementias, i.e. a frequency of 13.0%. Of the 32 demented patients, 21 (65.6%) had vascular dementia and 34.4% had degenerative dementia. We did not note a mixed etiology. Dementia was severe in 15.6% of cases. In multivariate analysis, only age (OR = 10.09; 95% CI [4.19 - 24.27]; p < 0.001), arterial hypertension (OR = 7.10; 95% CI [1.92 - 26.22]; p = 0.003), and alcohol consumption (OR = 3.95; 95% CI [1.29 - 12.15]; p = 0.017) were statically associated with the onset of dementia in our diabetic patients. Conclusion: Screening for dementia should be systematic in diabetics, especially at old age.
Keywords: Dementia; Diabetes; Porto-Novo; Benin